An open‐label, dose‐ranging study of Rolontis, a novel long‐acting myeloid growth factor, in breast cancer. (23rd March 2018) - Vacirca, Jeffrey L.; Chan, Arlene; Mezei, Klára; Adoo, Clarence S.; Pápai, Zsuzsanna; McGregor, Kimberly; Okera, Meena; Horváth, Zsolt; Landherr, László; Hanslik, Jerzy; Hager, Steven J.; Ibrahim, Emad N.; et al.
Abstract: This randomized, open‐label, active‐controlled study investigated the safety and efficacy of three doses of Rolontis (eflapegrastim), a novel, long‐acting myeloid growth factor, versus pegfilgrastim in breast cancer patients being treated with docetaxel and cyclophosphamide (TC). The primary efficacy endpoint was duration of severe neutropenia (DSN) during the first cycle of treatment. Patients who were candidates for adjuvant/neoadjuvant TC chemotherapy were eligible for participation. TC was administered on Day 1, followed by 45, 135, or 270 μ g/kg Rolontis or 6 mg pegfilgrastim on Day 2. Complete blood counts were monitored daily when the absolute neutrophil count (ANC) fell to <1.5 × 10 9 /L. Up to four cycles of TC were investigated. The difference in DSN (time from ANC <0.5 × 10 9 /L to ANC recovery ≥2.0 × 10 9 /L) between the Rolontis and pegfilgrastim groups was −0.28 days (confidence interval [CI]: −0.56, −0.06) at 270 μ g/kg, 0.14 days (CI: −0.28, 0.64) at 135 μ g/kg, and 0.72 days (CI: 0.19, 1.27) at 45 μ g/kg. Noninferiority to pegfilgrastim was demonstrated at 135 μ g/kg ( P = 0.002) and 270 μ g/kg ( P < .001), with superiority demonstrated at 270 μ g/kg (0.03 days; P = 0.023). The most common treatment‐related adverse events (AEs) were bone pain, myalgia, arthralgia, back pain, and elevated white blood cell counts, with similar incidences across groups. All doses of Rolontis were well tolerated, and no new or significant treatment‐related toxicities were observed. In Cycle 1, Rolontis demonstrated noninferiority at the 135 μ g/kg dose and statistical superiority in DSN at the 270 μ g/kg dose when compared to pegfilgrastim. Abstract : The trial demonstrates that Rolontis conferred comparable efficacy benefits to pegfilgrastim in duration of severe neutropenia and presented no unknown safety concerns when administered to patients with breast cancer receiving docetaxel and cyclophosphamide as adjuvant or neoadjuvant chemotherapy.